2000
DOI: 10.1128/jvi.74.7.3227-3234.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Relationships of Endemic/Epidemic and Sylvatic Dengue Viruses

Abstract: Endemic/epidemic dengue viruses (DEN) that are transmitted among humans by the mosquito vectors Aedes aegypti and Aedes albopictus are hypothesized to have evolved from sylvatic DEN strains that are transmitted among nonhuman primates in West Africa and Malaysia by other Aedes mosquitoes. We tested this hypothesis with phylogenetic studies using envelope protein gene sequences of both endemic/epidemic and sylvatic strains. The basal position of sylvatic lineages of DEN-1, -2, and -4 suggested that the endemic/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
298
0
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 362 publications
(332 citation statements)
references
References 39 publications
15
298
0
12
Order By: Relevance
“…DENV-1-4 evolved in non-human primates from a common ancestor and each entered the urban cycle independently an estimated 500-1,000 years ago 12 . The virion comprises a spherical particle, 40-50 nm in diameter, with a lipopolysaccharide envelope.…”
Section: Dengue Virus Pathogenesismentioning
confidence: 99%
“…DENV-1-4 evolved in non-human primates from a common ancestor and each entered the urban cycle independently an estimated 500-1,000 years ago 12 . The virion comprises a spherical particle, 40-50 nm in diameter, with a lipopolysaccharide envelope.…”
Section: Dengue Virus Pathogenesismentioning
confidence: 99%
“…These models have shown that specific dengue virus genetic variants or genotypes have established transmission cycles on other continents, are responsible for outbreaks of more severe disease (DHF/DSS) and have helped track the displacement of one genotype by another, more virulent genotype. However, some of these algorithms have also been used to extrapolate on the occurrence of intramolecular recombination in dengue RNA genomes [44], the ancient origin of epidemic strains [45] and the movement of genotypes within a country or from one country to another [46], without the support of molecular studies of viruses or sufficient field sampling and epidemiologic studies of the transmission cycles. Therefore, it is unclear whether these phenomena actually occur in nature.…”
Section: In Silico Modelsmentioning
confidence: 99%
“…DENV is a member of Flaviviridae family and is transmitted to humans by infected female Aedes genus, especially Aedes aegypti or Aedes albopictus [3,4] . There are four serotypes of dengue virus (DENV [1][2][3][4] that manifest with similar symptoms [5,6] . Two types of infections are caused by DENV, namely, primary infection and secondary infection.…”
Section: Introductionmentioning
confidence: 99%